Development of Waqf Objects through Public Private Partnership (PPP) as a Means of Infrastructure Development for the Public Interest - H. Noho, Muhammad Dzikirullah (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2023)
Waqf as an amaliyah service should be an instrument to improve the welfare of the wider community. Various waqf cases in the Religious Courts can be a reflection for the future so that the objects that have been pledged can be fit for their intended purpose. With a public private partnership (PPP) scheme, existing waqf objects will be more optimally developed. To follow up on efforts to develop waqf objects, research was carried out using a type of normative legal research that relies on related principles and norms. The legal materials used are primary legal materials in the form of decisions and statutory regulations related to waqf and PPP. Meanwhile, the secondary legal materials used are journals and books on waqf law, PPP, and land acquisition for development in the public interest. The results of the research found that so far efforts to develop waqf objects are still very minimal, on the other hand, there are also government provisions through Law 2/2012 PTBPUKU which require citizens to surrender their land rights if they are affected by construction for the public interest. This provision is in line with Law 41/2004 concerning Waqf which requires that waqf objects can be used for public purposes as long as they obtain permission from the Minister through the waqf body. Apart from that, in the context of development for the public interest and development of waqf objects, the government often uses the PPP model to financially optimize waqf objects. The most ideal scheme to use in increasing waqf objects can be carried out in the form of PPP in the form of BOT, BOOT or ROOT. Its use and designation are adjusted to the permits and designation of the waqf pledge as stated in statutory regulations and sharia principles.